Pan‐dermatophyte PCR. (3rd June 2019) - Walser, M.; Bosshard, P.P.
Summary: Dermatophytes are fungi that cause infections of the skin, hair and nails, called dermatophytosis or ringworm. These infections are among the most common skin diseases and affect up to 20% of the population at any given time. Current laboratory diagnosis of dermatophytosis is still based on microscopy and culture. Culture means taking samples and growing them in a lab and microscopy means examining samples under a microscope. This can be cumbersome and time‐consuming (the culture for dermatophytes takes up to four weeks). In this study from Switzerland, the authors aimed to establish a simple, robust, and rapid test that allows them to detect dermatophytes in samples within 1 to 2 days. They developed a type of test called a polymerase chain reaction (PCR) assay, which makes many copies of specific dermatophyte DNA in a test tube, making it possible to prove the presence of the DNA in the sample (specimen). The PCR assay was evaluated using 306 clinical specimens (nails, skin and hairs) by comparing it to the results of microscopy and culture. Sensitivities (proportions of actual positives that are correctly identified as such) were estimated to be 96.9% for PCR, 46.7% for culture and 91.4% for microscopy while specificities (proportions of actual negatives that are correctly identified as such) were estimated to be 90.4%, 98.7%, and 84.0%, respectively. The new assay showed excellent performance and is significantly faster than culturing techniques, making it very promising for diagnosing dermatophytosis. Abstract : Linked Article: Walser and Bosshard et al. Br J Dermatol 2019; 180 :1489–1497